Indoles: metabolites produced by intestinal bacteria capable of controlling liver disease manifestation. (14th March 2019) - Hendrikx, T.; Schnabl, B.
Abstract: Alterations in the bacteria that reside in our gastrointestinal tract play a role in the pathogenesis and progression of many disorders including liver and gastrointestinal diseases. Both qualitative (composition) and quantitative (amount) changes in gut microbes are associated with increased susceptibility to liver disease. Importantly, the intestinal microbiota is involved in the regulation of many host signalling pathways via the generation of different metabolites. Hence, dysbiosis influences disease development and progression by directly affecting the host–bacteria metabolic interaction. Microbe‐derived harmful metabolites can translocate to distant organs due to increased intestinal permeability as observed during dysbiosis. Contrary, certain bacterial metabolites such as tryptophan metabolites contribute to intestinal and systemic homeostasis. Here, we provide an overview of current evidence describing to what extent microbial metabolites modulate the development of chronic liver diseases such as alcoholic steatohepatitis and nonalcoholic fatty liver disease with a special emphasis on indoles. Abstract :